Simulation on reactor TRIGA Puspati core kinetics fueled with thorium (Th) based fuel element - Mohammed A.A.; Pauzi A.M.; Rahman S.M.H.A.; Zin M.R.M.; Jamro R.; Idris F.M. (American Institute of Physics Inc., 2023)
In confronting global energy requirement and the search for better technologies, there is a real case for widening the range of potential variations in the design of nuclear power plants. Smaller and simpler reactors are attractive, provided they can meet safety and security standards and non-proliferation issues. On fuel cycle aspect, thorium fuel cycles produce much less plutonium and other radioactive transuranic elements than uranium fuel cycles. Although not fissile itself, Th-232 will absorb slow neutrons to produce uranium-233 (233U), which is fissile. By introducing Thorium, the numbers of highly enriched uranium fuel element can be reduced while maintaining the core neutronic performance. This paper describes the core kinetic of a small research reactor core like TRIGA fueled with a Th filled fuel element matrix using a general purpose Monte Carlo N-Particle (MCNP) code. 2016 AIP Publishing LLC.